Integrated bulk and single-cell RNA sequencing reveals a cuproptosis-related LncRNA prognostic signature in neuroblastoma - Ke Chen; Jing Wang; Shimin Yang; Jun Xiao; Luyao Wu; Zejian Li; Xiang Zhao; Xuyong Chen; Honglin Li; Jiexiong Feng; Xinyao Meng (BMC Cancer)
Abstract Background Neuroblastoma (NB), the most common extracranial solid tumor of childhood, originates from developing sympathetic nervous system. While cuproptosis has emerged as a critical regulator in oncobiology, its mechanistic involvement in NB remains poorly characterized. Methods RNA-seq data of NB patients was analyzed using limma and ClusterProfiler. CRlncRNAs were identified through Pearson correlation between lncRNAs and CRGs, with co-expression networks visualized via ggalluvial. Prognostic signature was constructed through Lasso-penetrated Cox regression and validated via EFS analysis, C-index, and ROC curves. Somatic mutations and TMB were profiled using maftools. Immune infiltration landscapes were deciphered by CIBERSORT, while single-cell analysis integrated AddModuleScore, AUCell, and inferCNV to map CNV-driven transcriptional heterogeneity. Functional validation via siRNA knockdown confirmed the oncogenic role of CRGs. Results The risk model: Risk Score = (-1.637×DIRC3-AS1) + (0.6758×FOXN3-AS1) + (0.3032×LINC00682) + (-0.6812×RASSF8-AS1) was constructed. Stratification by median risk score revealed significantly prolonged EFS and OS. No significant TMB difference was observed between subgroups. scRNA-seq analysis highlighted malignant cell dominance with marked CNVs in high-risk patients. Functional validation confirmed CRlncRNAs’ roles in modulating proliferation and migration. Conclusion Our findings establish a novel prognostic framework for NB that enhances risk stratification accuracy and provides actionable biomarkers to guide precision clinical management.